The Right to be Wrong: Examining the (Im) possibilities of Regulating Fake News while Preserving the Freedom of Expression in Kenya - Sugow, Abdulmalik (Strathmore Law Review, 2019)
With the proliferation of peer-to-peer networks as a source of information, concerns on the accuracy of information shared have been raised, necessitating attempts by governments to regulate fake news. Kenya’s Computer Misuse and Cybercrimes Act, for instance, criminalises the intentional dissemination of false or misleading data. However, such regulation has resulted in a different set of concerns, particularly its potential to bring about undue limitation on the freedom of expression. In appraising the approach taken in Kenya of imposing liability on perpetrators, and that taken in some jurisdictions of imposing intermediary liability, the article posits that similar difficulties are faced in regulating fake news – the freedom of expression could be curtailed. This is fuelled by ambiguity in the definition of ‘fake news’. Consequently, this article seeks to find out if indeed, it is possible to regulate fake news while preserving the freedom of expression in Kenya. Further, the article delves into some of the effects the proliferation of fake news has had on the democratic process in Kenya, thereby requiring regulation. In doing so, it tackles fake news from two general conceptions: fake news as calculated disinformation campaigns by individuals for certain purposes, and fake news as an overarching culture of misinformation that enables the spread of false information. Regarding the former, it finds that legislative measures may prove sufficient. However, the latter requires a combination of non-legislative measures such as collaborative measure, awareness initiatives and fact-checking.